THE ROLE OF PROACTIVE LEADERSHIP IN ACHIEVING THE STRATEGIC RESPONSE-AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES OF THE GENERAL COMPANY FOR GAS FILLING AND SERVICES / SALAH AL-DIN BRANCH (World Economics and Finance Bulletin, 2023)
The current study aimed to identify the role of proactive leadership in achieving strategic response among a sample of employees of the General Company for Gas Filling and Services/Salah Al-Din Branch
Keywords: proactive leadership; strategic response; General Company for Gas Filling and Services